Odpowiedzi

Najlepsza Odpowiedź!
2010-03-26T00:29:17+01:00
A) f(x)=x²-6x+8
Δ=b²-4*a*c=(-6)²-4*1*8=36-32=4
√Δ=2
x₁=(-b-√Δ)/2a= (6-2)/2=4/2=2
x₂=(-b+√Δ)/2a=(6+2)/2=8/2=4
f(x)=a(x-x₁)(x-x₂) --wzór na postać iloczynową
f(x)=(x-2)(x-4) ---postać iloczynowa
p=-b/2a=6/2=3
q=-Δ/4a=-4/4=-1
f(x)=a(x-p)²+q ---wzór na postać kanoniczna
f(x)=(x-3)²-1 --- postać kanoniczna

b) f(x)= - ⅓x² + 4x
Δ=b²-4*a*c= 4²-4*(-⅓)*0=16
√Δ=4
x₁=(-b-√Δ)/2a=(-4-4)/-⅔=12
x₂=(-b+√Δ)/2a=(-4+4)/-⅔=0
f(x)=a(x-x₁)(x-x₂) --wzór na postać iloczynową
f(x)=-⅓(x-12)(x+0) ---posatc iloczynowa
p=-b/2a=-4/-⅔=6
q=-Δ/4a=-16/-(4/3)=12
f(x)=a(x-p)²+q ---wzór na postać kanoniczna
f(x)=-⅓(x-6)²+12 ---postac kanoniczna
10 4 10